Business Plan to Startup a Vietnamese Cafe: case: the Vietnam Cafe in Rovaniemi - Nguyen, Thi Kim Hieu (2022)
This business plan is set to help the author achieve a clear picture of running a business - a Vietnamese café in Rovaniemi as well as Finland. Finland is ranked the second-highest nation which has a large demand for coffee consumption. Therefore, it is viable to open a coffee shop in Rovaniemi as well as in Finland due to this high demand for coffee utilization. In order to achieve a crystal view of the business plan and those factors which affect a business theoretical and empirical studies were carried out to comprehend the theories of linked terms of the issue and analyze the primary business concepts of the café. The thesis applies a qualitative research method: participant observation and semi-structured interviews to gather data. Moreover, statistics were collected from secondary data such as official websites and Finnish national web pages. Moreover, the literature resources are obtained via the use of published materials such as books and web articles. As a result, a development foundation of the business plan was created, which comprises the aspect of Finnish’ PEST, the cafe’s potential competitors, business model canvas, SWOT, and marketing strategy. However, the financial strategy was not meticulously resolved, and the business plan is a draft. The research and information can potentially be useful for anyone who plans to conduct the same research or preparation for a Vietnamese café business to launch.